1995
DOI: 10.2307/3236344
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of seedling recruitment in West‐Mediterranean Quercus ilex forest influenced by canopy development

Abstract: Quercus ilex (holm oak) coppice forests belong to the most representative communities in the western part of the Iberian Peninsula. Due to the high sprouting potential of holm oak after coppicing, the dynamics of recruitment of new individuals in existing populations has been largely overlooked. In these forests, the density of seedlings increases in old stands, as a result of the remarkable increase in the recruitment of 1-yr and 2-yr old seedlings, probably due to better environmental conditions for germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
114
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 31 publications
6
114
0
3
Order By: Relevance
“…Seedling populations in holm oak forests show large variability across different spatial scales [12,24]. The causes of this variability are various, and not always easy to explain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Seedling populations in holm oak forests show large variability across different spatial scales [12,24]. The causes of this variability are various, and not always easy to explain.…”
Section: Discussionmentioning
confidence: 99%
“…For the range of conditions considered, the time of development from young seedlings to old seedlings and, later, to saplings, is very difficult to determine. In the same Montseny massif, Espelta et al [12] analysed 1-to 12-year-old seedlings, and found very limited growth during the first four years, and slightly faster growth thereafter. Nevertheless, it is quite difficult to extrapolate this information, based on the estimation of seedling age by counting the total number of terminal bud scars on the leading shoot.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations